Analysis of Argonaute Complex Bound mRNAs in DU145 Prostate Carcinoma Cells Reveals New miRNA Target Genes. (5th January 2017) - Szczyrba, Jaroslaw; Jung, Volker; Beitzinger, Michaela; Nolte, Elke; Wach, Sven; Hart, Martin; Sapich, Sandra; Wiesehöfer, Marc; Taubert, Helge; Wennemuth, Gunther; Eichner, Norbert; Stempfl, Thomas; et al.
Abstract : Posttranscriptional gene regulation by microRNAs (miRNAs) contributes to the induction and maintenance of prostate carcinoma (PCa). To identify mRNAs enriched or removed from Ago2-containing RISC complexes, these complexes were immunoprecipitated from normal prostate fibroblasts (PNFs) and the PCa line DU145 and the bound mRNAs were quantified by microarray. The analysis of Ago complexes derived from PNFs or DU145 confirmed the enrichment or depletion of a variety of mRNAs already known from the literature to be deregulated. Novel potential targets were analyzed by luciferase assays with miRNAs known to be deregulated in PCa. We demonstrate that the mRNAs of the death effector domain-containing protein (DEDD), the tumor necrosis factor receptor superfamily, member 10b protein (TNFRSF10B), the tumor protein p53 inducible nuclear protein 1 (TP53INP1), and the secreted protein, acidic, cysteine-rich (SPARC; osteonectin) are regulated by miRNAs miR-148a, miR-20a, miR-24, and miR-29a/b, respectively. Therefore, these miRNAs represent potential targets for therapy. Surprisingly, overexpression of miR-24 induced focus formation and proliferation of DU145 cells, while miR-29b reduced proliferation. The study confirms genes deregulated in PCa by virtue of their presence/absence in the Ago2-complex. In conjunction with the already published miRNA profiles of PCa, the data can be used to identify miRNA-regulated mRNAs.